CHILDREN WITH AUTISM SPECTRUM DISORDER (ASD): A SYSTEMATIC REVIEW STUDY (CIPEEX, 2026)
Introduction: Autism Spectrum Disorder (ASD), classified by the DSM-5 as a neurodevelopmental disorder, is characterized by restricted patterns and difficulties in communication and social interaction, with emotional, cognitive, motor, and sensory manifestations beginning in childhood. Although motor development is not a diagnostic criterion, studies indicate that motor deficits are frequently present and impact cognitive, linguistic, and social aspects, making early recognition of these characteristics essential for effective intervention. Objectives: To determine whether the motor deficits presented by children with autism spectrum disorder can impact other areas of development. Methodology: This is a systematic literature review with a qualitative approach, based on the interpretation of scientific studies addressing motor development in children with ASD. Results: The results showed that approximately 88.6% of the participants were male. Motor delays were observed in up to 90% of cases, with impairment in fine (38.5%) and gross (6.7%) motor skills. Furthermore, 83.7% presented cognitive impairment and 81.8% presented below-average mental performance. Regarding motor function, the averages were 81.73% for posture and 75.91% for locomotion. Dyspraxia was identified in 100% of cases evaluated through hippotherapy. The data demonstrate a correlation between initial motor deficits and impairments in language, communication, and functional autonomy. Conclusion: Children with ASD present motor and cognitive delays that affect their development. Early intervention is essential to minimize these impacts. Further research should include larger sample sizes and ongoing monitoring.
Keywords: transtorno do espectro autista; distúrbios da habilidade motora; desempenho psicomotor